Production of polycarbonate and multi -walled carbon nanotubes nanocomposites at low filler loadings - Al-Timimi, Buthaniah Ali Abed (2015)
Polymer nanocomposites are the materials of the future, which will change the course of all industries, since polymers today find their applications in every industry. Multiwalled carbon nanotubes (MWCNTs) had been widely used for filler for various nanocomposites. Thus, this research focuses on the fabrication of polycarbonate (PC) /multi-walled carbon nanotubes (MWCNTs) nanocomposites. The objectives of the work were to study the physico-chemical properties of multi-walled carbon nanotubes produced by the modified Staudenmaier method. The mechanical, thermal, electrical and chemical properties of nanocomposites produced with different filler loadings were also assessed. The gasoline absorption capabilities of the nanocomposites were also conducted. The modified Staudenmaier method was used to produce the multi-walled carbon nanotubes (MWCNTs) used in this work. The produced carbon nanotubes were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA) and Raman analysis. The MWCNTs were then mixed with the PC to produce PC/ MWCNTs nanocomposites. The operating parameters of the mixer were varied for best operating conditions to produce the nanocomposites based on tensile data of the products. The effects of filler loading, ranges from 0–1 wt.% , on the properties of the nanocomposites were also investigated. The mechanical, thermal, and electrical properties as well as chemical resistance performance of the nanocomposites were evaluated. Multivariate analysis of variance (MANOVA) was applied to assess the significance improvement that had been introduced in this work. The produced multi-walled carbon nanotubes (MWCNTs) have a diameter of 13.1nm.The yield is approximately 10% of the carbon source (graphite). The work contributes knowledge on the effects of adding low filler (MWCNTs) loadings on the properties of polymer; in particular, PC/MWCNTs nanocomposites. It shows the potentials of PC/MWCNTs as suitable material for gasoline storage due to its high gasoline absorption resistance and can be a material of choice in the future.